8 - RSE et justice sociale : le cas des multinationales pétrolières dans le Delta du Niger - Lado, Hervé; Renouard, Cécile (Africa Development, 2021)
The assumptions that have underpinned the modern conception of social justice appear irrelevant in the presence of weak institutions. Issues of justice are no longer raised in the context of a sovereign nation-state and of goods being distributed among citizens with equal rights. Nor are they raised in the context of societies with relatively homogeneous claims. Focusing on the context of Nigeria’s Niger Delta and on the corporate social responsibility (CSR) practices of oil multinationals (MNCs) vis-à-vis local communities affected by oil operations, we show how the local traditional conception of justice relative to property rights leads to a deterioration of the social fabric, whilst also fostering the emergence of social, political and economic inequalities that undermine democratic notions of justice. We then build on a critique of the ideas of Michael Walzer and Amartya Sen, asserting that a set of unjust practices can be identified and recognized by the various parties involved (namely, communities and civil society organizations, as well as MNCs and governmental institutions); or at least by social critics within them. Finally, we suggest the conditions necessary for a more just social order adapted to local realities; one that would bring together the various stakeholders in an endogenous transformative action.